Development of an evidence-based ESCALATION system for recognition and response to paediatric clinical deterioration - Gill, Fenella; Cooper, Alannah; Falconer, Pania; Stokes, S.; Leslie, Gavin (ELSEVIER SCIENCE INC, 2021)
Aim: The aim of this study was to develop an evidence-based paediatric early warning system for infants and children that takes into consideration a variety of paediatric healthcare contexts and addresses barriers to escalation of care. Methods: A three-stage intervention development framework consisted of Stage 1: evidence review, benchmarking, stakeholder (health professionals, decision-makers, and health consumers) engagement, and consultation; Stage 2: planning and coproduction by the researchers and stakeholders using action research cycles; and Stage 3: prototyping and testing. Results: A prototype evidence-based system incorporated human factor principles, used a structured approach to patient assessment, promoted situational awareness, and included family as well as clinician concern. Family involvement in detecting changes in their child's condition was supported by posters and flyers codesigned with health consumers. Five age-specific observation and response charts included 10 weighted variables and one unweighted variable (temperature) to convey a composite early warning score. The escalation pathway was supported by a targeted communication framework (iSoBAR NOW). Conclusion: The development process resulted in an agreed uniform ESCALATION system incorporating a whole-system approach to promote critical thinking, situational awareness for the early recognition of paediatric clinical deterioration as well as timely and effective escalation of care. Incorporating family involvement was a novel component of the system.